REDESAIN RANGKA MUATAN MOBIL ROAD SWEEPER - Muhamad Zuhri Alfaridz (2024)
Previously, the frame of the road sweeper used Hollow Steel ASTM A500 material and an inefficient design, leading to operational failures in waste compaction. Therefore, a redesign is necessary to address these issues. To achieve an effective design, Finite Element Analysis (FEA) is employed in this research, utilizing Solidworks 2022 SP5 software. The use of V slot rails in the compaction frame aims to prevent operational failures. Simulation results show that each redesign model, using different materials (ASTM A500, Aluminium Alloy 6061, and Aluminium Alloy 6063), experiences a weight reduction. All three designs are deemed safe for the calculated loads. The redesign of ASTM A500 emerges as the best design due to a significant weight reduction compared to the original design and a more cost-effective material compared to Aluminium Alloy 6061 and 6063.